2007
DOI: 10.1038/sj.jid.5700616
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 Is Expressed in Melanoma Cells and Is Upregulated in TGF-Beta Stimulated Mast Cells

Abstract: Many studies detect elevated numbers of mast cells in tumors, but it is still controversial whether they are beneficial or detrimental for tumor cells. Furthermore, many tumors, such as melanomas, produce large quantities of transforming growth factor (TGF)-beta and during tumorigenesis the apoptotic and growth-inhibitory effects of TGF-betas are lost. Based on these data we investigated the gene expression changes in TGF-betaI-treated human mast cells with DNA microarray and detected 45 differentially regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 40 publications
(50 reference statements)
10
95
0
Order By: Relevance
“…[27][28][29] While PD-1 was only expressed on tumor cells in 10% of the unpretreated samples, TIM-3 expression was observed on tumor cells in both unpretreated and pretreated samples. More unpretreated samples had TIM-3 C TILs compare with the pretreated, taken into consideration that our number of pretreated samples is rather low.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] While PD-1 was only expressed on tumor cells in 10% of the unpretreated samples, TIM-3 expression was observed on tumor cells in both unpretreated and pretreated samples. More unpretreated samples had TIM-3 C TILs compare with the pretreated, taken into consideration that our number of pretreated samples is rather low.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of TIM-3 expression has been reported in T cells stimulated with anti-CD3 antibody together with anti-CD28 antibody, and in human primary mast cells treated with TGF-␤ (Hastings et al, 2009;Wiener et al, 2007). To find regulatory molecules for induction of TIM-3 transcription, we analyzed TIM-3 mRNA levels in Jurkat T cells and HMC-1 human mast cells after stimulation with PMA and TGF-␤.…”
Section: Induction Of Tim-3 Transcription In Jurkat T Cells and Hmc-1mentioning
confidence: 99%
“…Its expression has been revealed in many other immune cells including macrophages, dendritic cells, natural killer (NK) cells and mast cells (Ju et al, 2010;Sabatos et al, 2003;Wiener et al, 2007). TIM-3 plays important roles in immune responses by modulating functions of these cells through interaction with its ligands: galectin-9 and/or phosphatidyl serine (Nakayama et al, 2009;Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have demonstrated the expression of Tim-3 in other types of cells (10)(11)(12). Moreover, the up-regulation of Tim-3 has been confirmed in different inflammatory diseases (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%